Protective efficacy of a trivalent recombinant hemagglutinin protein vaccine (FluBlok®) against influenza in healthy adults: A randomized, placebo-controlled trial - Treanor, John J.; Sahly, Hana El; King, James; Graham, Irene; Izikson, Ruvim; Kohberger, Robert; Patriarca, Peter; Cox, Manon (Vaccine, 2011)
► Randomized, placebo-controlled, multicenter assessment of efficacy of baculovirus expressed hemagglutinin vaccine for prevention of laboratory-documented influenza illness in healthy adults. ► Vaccine was safe and generated serum hemagglutination-inhibiting antibody responses against all three components in the majority of recipients. ► Influenza infections during surveillance were antigenically mismatched to the components in the vaccine. ► Vaccine efficacy was 44.8% (95% CI, 24.4%, 60.0%) for prevention of preventing culture-confirmed influenza illness. Development of influenza vaccines that do not use embryonated eggs as the substrate for vaccine production is a high priority. We conducted this study to determine the protective efficacy a recombinant, baculovirus-expressed seasonal trivalent influenza virus hemagglutinin (rHA0) vaccine (FluBlok®). Healthy adult subjects at 24 centers across the US were randomly assigned to receive a single injection of saline placebo (2304 subjects), or trivalent FluBlok containing 45 mcg of each rHA0 component (2344 subjects). Serum samples for assessment of immune responses by hemagglutination-inhibition (HAI) were taken from a subset of subjects before and 28 days after immunization. Subjects were followed during the 2007–2008 influenza season and combined nasal and throat swabs for virus isolation were obtained from subjects reporting influenza-like illness. Rates of local and systemic side effects were low, and the rates of systemic side effects were similar in the vaccine and placebo groups. HAI antibody responses were seen in 78%, 81%, and 52% of FluBlok recipients to the H1, H3, and B components, respectively. FluBlok was 44.6% (95% CI, 18.8%, 62.6%) effective in preventing culture-confirmed influenza meeting the CDC influenza-like illness case definition despite significant antigenic mismatch between the vaccine antigens and circulating viruses. Trivalent rHA0 vaccine was safe, immunogenic and effective in the prevention of culture confirmed influenza illness, including protection against drift variants.